A high-speed secure quantum random number generator based on vacuum states - Gabriel, Christian; Wittmann, Christoffer; Hacker, Bastian; Mauerer, Wolfgang; Huntington, Elanor; Sabuncu, Metin; Marquardt, Christoph; Leuchs, Gerd (2012 Conference on Lasers and Electro-Optics, CLEO 2012, 2012)
A high-speed continuous-variable quantum random bit generator with an expected effective bit generation rate of up to 10 GBit/s is presented. The obtained bit sequences are truly random and unique, i.e. they cannot be known by an adversary. © 2012 OSA.
CRIS-Team Scopus Importer:2022-06-05

Cluster state generation with quadrature squeezed cylindrically polarized modes - Gabriel, Christian; Rigas, Ioannes; Aiello, Andrea; Berg-Johansen, Stefan; van Loock, Peter; Marquardt, Christoph; Leuchs, Gerd (2012 Conference on Lasers and Electro-Optics, CLEO 2012, 2012)
We present schemes which exploit the hybrid-entanglement in quadrature squeezed cylindrically polarized modes to generate cluster states. Such states are essential for one-way quantum computing. © 2012 OSA.
CRIS-Team Scopus Importer:2022-06-05